Efektivitas Layanan Informasi Karier untuk Meningkatkan Perencanaan Karier Siswa SMA - Silvia Yula Wardani; Rischa Pramudia Trisnani (Universitas Mathla'ul Anwar Banten, 2019)
THE EFFECTIVENESS OF CAREER INFORMATION SERVICES TO IMPROVE CAREER PLANNING FOR HIGH SCHOOL STUDENTS. High School Education aims to prepare students who will continue their education to a higher level, while preparing students who will work immediately if they have completed their education in high school. Experiencee in the field shows that there are still many students who are confused about choosing the department (study program) to be entered, especially for high school students. The purpose of this study was to determine the effectiveness of information services to improve career planning for students of SMA Negeri 1 Nglames. The sampling technique used was purposive sampling. This research was conducted at SMA Negeri 1 Nglames with pre-experimental design research design. Data collection techniques use a psychological scale that is the scale of career planning. Data analysis techniques using t-test. The results showed effective information services to improve career planning proved after a hypothetical test with the t-test analysis technique of the value of asympsig (2-tailed)/asympiotic significance 0.000, it can be concluded that information services to improve career planning of students of SMA Negeri 1 Nglames Kabupaten Madiun.